1986
DOI: 10.1037/0033-2909.100.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Stress of predictable and unpredictable shock.

Abstract: This article examines the claim that unpredictable shock is more stressful than predictable shock in short-term studies (Abbott, Schoen, & Badia, 1984). These authors' classification of studies as short or long term, their conceptualization of them as predictability studies, and their failure to note contrary evidence are discussed. The conclusion is that predictable shock (the presence of a warning signal before shock) makes the situation more stressful both in short-and long-term studies. Conflicting results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Using an operant paradigm, female and male rats were tested for drug SA with and without predictable or unpredictable acute and repeated stress. Consistent with earlier behavioral, immunological, and physiological reports (Abbott et al , 1984;Arthur, 1986;Glass & Singer, 1972;McKinnon et aI., 1989), predictability had a different effect on drug SA depending on whether the stressor was acute or chronic. Specifically, predictability of the stressor increased fentanyl SA with repeated exposure to the stressor, especially for female subjects.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Using an operant paradigm, female and male rats were tested for drug SA with and without predictable or unpredictable acute and repeated stress. Consistent with earlier behavioral, immunological, and physiological reports (Abbott et al , 1984;Arthur, 1986;Glass & Singer, 1972;McKinnon et aI., 1989), predictability had a different effect on drug SA depending on whether the stressor was acute or chronic. Specifically, predictability of the stressor increased fentanyl SA with repeated exposure to the stressor, especially for female subjects.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Glass and Singer (1972) reported a series of human laboratory studies which found that predictability of a noise stressor attenuated the performance decrements that occurred after cessation of an acute unpredictable nois8 stressor . In contrast, under conditions of chronic stressor exposure, predictability potentiated behavioral , physiological, biochemical, and immunological stress responses (Abbott, Schoen, & Badia, 1984;Arthur, 1986;McKinnon, Weisse, Reynolds, Bowles, & Baum, 1989). This increase with repeated exposure to a stressor might reflect: (1) sensitization to the stressor; or (2) classical conditioning between the stimuli that predict the stressor and the stressor itself ( Pavlov, 1906;Rescorla, 1966;Rescorla, 1967).…”
Section: Predictability Of a Stressormentioning
confidence: 99%
See 2 more Smart Citations
“…Third, studies have used preference testsgiving the animals choice between, for example, predictable and unpredictable electric shock. These tests provide a clear indication of the animals' preference, but they are not without their critics (Arthur, 1986, and see Fraser and Matthews, 1997 for a review).…”
Section: Measurement Of Welfarementioning
confidence: 99%